2016
DOI: 10.1007/s00262-016-1889-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of PD-L1 and PD-1 expression on tumor and immune cells in non-small cell lung cancer (NSCLC) using non-enzymatic tissue dissociation and flow cytometry

Abstract: Comparing the IncellPREP homogenization and FNA demonstrated a strong correlation (r - 0.8) for expression of PD-L1. We compared PD-L1 expression by flow cytometry using a 1 % cutoff for positivity in the tumor cell population and a 1 % cutoff of cells with at least 1+ intensity in immunohistochemically stained tissue sections as positive. Ten of 12 lung tumor samples were concordant while 2 were discordant. PD-L1 expression by flow cytometry varied widely (1.2-89.4 %) even in the positive concordant cases. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The SPC11 cell line (positive by FACS) was weakly positive only in one of the three samples (untreated, treated with gemcitabine, or treated with cisplatin/pemetrexed). This is consistent with reports showing variation among different PD-L1 antibodies (32) and that PD-L1 analysis by FACS and IHC is not fully overlapping (33).…”
Section: Chemotherapy Does Not Influence Pd-l1 Expression By Human Mesupporting
confidence: 93%
“…The SPC11 cell line (positive by FACS) was weakly positive only in one of the three samples (untreated, treated with gemcitabine, or treated with cisplatin/pemetrexed). This is consistent with reports showing variation among different PD-L1 antibodies (32) and that PD-L1 analysis by FACS and IHC is not fully overlapping (33).…”
Section: Chemotherapy Does Not Influence Pd-l1 Expression By Human Mesupporting
confidence: 93%
“…In previous studies, the same methodology has been used to examined the PD-L1 expression on tumor cells and immune cells isolated from nonsmall lung cancer specimens [20,21]. They showed that the results of flow cytometric detection of PD-L1 were highly concordant with the results using IHC and proposed that the differential quantification of PD-L1 on tumor cells and immune cells may allow for better prediction of response to anti-PD-1/PD-L1 antibody therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, comprehensive investigations have shown that immune components contribute to tumor progression and are strong predictors in patients with solid malignancies [17]. The recent success of immune checkpoint inhibitors such as programmed death-1 (PD-1) and programmed death-ligand 1 (PD-L1) blocking antibodies in clinical trials [813] greatly impacted treatment strategies of several malignancies.…”
Section: Introductionmentioning
confidence: 99%